Evaluation of Peel Plate™ EC for Determination of E. coli and Coliform or Total Coliform in Dairy Products. (27th November 2019) - Salter, Robert S; Durbin, Gregory W; Bird, Patrick; Fisher, Kiel; Crowley, Erin; Chen, Yi; Clark, Dorn; Ziemer, Wayne
Abstract: Peel Plate™ EC is a low-profile plastic, 47 mm culture dish with an adhesive top that contains a dried medium with Gram-negative selective agents and with enzyme substrate indicators for β-galactosidase (coliform) and β-glucuronidase ( Escherichia coli ). The method provides a conventional quantitative coliform (red) and E. coli (blue/purple/black) count with simple rehydration and incubation for 24 ± 2 h at 35 ± 1°C, while providing a total coliform result, sum of E. coli, and coliform without color differential in dairy products at 32 ± 1°C for 24 ± 2 h. Dairy matrixes claimed and supported with total coliform data are whole milk, skim milk, chocolate milk (2% fat), heavy cream (35% fat), pasteurized whole goat milk, ultra-high-temperature pasteurized milk, powdered milk, lactose-reduced milk, strawberry milk, shredded cheddar cheese, raw cow milk, raw goat milk, raw sheep milk, sour cream, condensed milk, eggnog, vanilla ice cream, condensed whey, yogurt, and cottage cheese. Matrixes claimed for E. coli and total coliform detection are raw ground beef, mixed cellulose 0.45 μm filtered bottled water, environmental sponge of stainless steel, raw ground turkey, dry dog food, liquid whole pasteurized eggs, milk chocolate, leafy green (mixed greens) rinse/flume water, irrigation water, poultry carcass rinse, and large animal carcass sponge. The method has been independently evaluated for total coliform in whole milk, skim milk, chocolate milk, and heavy cream. The method was also independently evaluated for E. coli and coliform in ground beef, filtered bottled water, and sponge rinse from stainless steel surfaces. In inclusivity and exclusivity studies, the method detected 57 of 58 different strains of coliform and E. coli at 32 ± 1°C and 35 ± 1°C in and excluded 31 of 32 different noncoliform strains consisting of Gram-negative and Gram-positive bacteria. In the matrix study, each matrix was assessed separately at each contamination level in comparison to an appropriate reference method. Colony counts were determined for each level and then log10 transformed. The transformed data were evaluated for repeatability, log-mean comparison between methods with 95% confidence interval, and r 2 . A 95% confidence interval range of −0.5 to 0.5 on the mean difference was used as the acceptance criterion to establish significant statistical difference between methods. The evaluations demonstrate that the Peel Plate EC method provides no statistical differences across most of the matrixes. The coliform r 2 values were greater than 0.9 except in the case of skim milk (r 2 = 0.77 and 0.69), sheep milk (0.84), and chocolate (0.81). In the case of skim milk, the three highest concentrations were significantly biased low compared with the reference method, whereas in the case of chocolate, the highest concentration was significantly biased high. The E. coli r 2 values were greater than 0.9 except in the case of hog rinse (0.89), flume water (0.82), and chocolate (0.77). The lower values were generally from only a 1 log difference between highest and lowest concentrations except in the case of chocolate, in which the highest concentration was biased high compared with the reference method. Within-method repeatability of Peel Plate EC was similar to the reference method, with relative SDs generally less than 5% when log10 means were ≥1.5. QC data support that the Peel Plate EC is stable for 1 year when refrigerated. Incubation temperature ranges, 30–36°C, and times, 22–26 and 48 h for yogurt, were not significantly different in paired t -test comparison. The method is selective without the need for confirmation, although confirmation of coliform and E. coli was performed as part of the validation work.